1997
DOI: 10.1093/carcin/18.11.2265
|View full text |Cite
|
Sign up to set email alerts
|

Development of esophageal metaplasia and adenocarcinoma in a rat surgical model without the use of a carcinogen

Abstract: In order to establish an animal model for studying the cause and prevention of esophageal adenocarcinoma (EAC) and its frequent precursor, Barrett's esophagus (BE), factors affecting the pathogenic processes were investigated in an esophagoduodenal anastomosis model with rats. Experiments by us and others have shown that surgical treatment produced reflux esophagitis with cell hyperproliferation, but not EAC. Additional treatment with a carcinogen has been shown to be necessary for the development of EAC, squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
121
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 36 publications
9
121
1
Order By: Relevance
“…12 As described earlier, all the EACs in the rat model were well-differentiated mucinous adenocarcinomas. 5,[10][11][12] In patients with BE variably differentiated adenocarcinomas are seen. In our study, only one of 11 human EACs was of the mucinous type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 As described earlier, all the EACs in the rat model were well-differentiated mucinous adenocarcinomas. 5,[10][11][12] In patients with BE variably differentiated adenocarcinomas are seen. In our study, only one of 11 human EACs was of the mucinous type.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] When chemical carcinogens are combined with surgically induced gastroesophageal reflux of gastrointestinal contents, mixed adenosquamous carcinomas are generally produced. 8,9 Goldstein et al 10 reported that rats with esophagoduodenal anastomosis develop EAC without adenosquamous or squamous cell carcinoma, and the frequency of carcinoma development increases by correction of postoperative anemia with parenteral iron therapy. Similarly, rats surgically treated with esophagogastroduodenal anastomosis (EGDA) to induce esophageal reflux of gastric acid and bile developed columnar-lined esophagus (CLE) and EAC in over half of the animals by 40 weeks after surgery.…”
mentioning
confidence: 99%
“…The importance of antioxidants in the treatment of reflux esophagitis comes also from the reported facts that oxidative damage has long been related to carcinogenesis in human cancers and animal cancer models [26][27][28][29] and oxidative damages have been reported to be related to columnar-lined esophagus, Barrett's esophagus. Reactive oxygen species increased with the grade of esophagitis and were reported to be the highest in Barrett's esophagus [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that animals such as mice, rats and rabbits can provide in vivo models for intestinal metaplasia of the esophagus (Vaezi et al, 1995;Goldstein et al, 1997;Ouatu-Lascar et al, 1999;Xu et al, 2000). Apart from the anatomo-pathologic observations and the evaluation of the severity of the lesions, the molecular mechanisms underlying the metaplastic process that take place in the esophagus cannot be investigated in these models.…”
mentioning
confidence: 99%